HF-Free Preparation, High Thermal and Color Stability of Mn4+ Activated K2TiF6 Red Phosphors for White Light-Emitting Diodes. (1st January 2018) - Pan, Xixiang; Hou, Dejian; Zhou, Ming; Lai, Haizhen; Ming, Hong; Ye, Xinyu
Abstract : Mn 4+ activated fluoride phosphors have been considered as highly promising red component for warm white light-emitting diodes in recent years. In this paper, we successfully prepared the K2 TiF6 : Mn 4+ red phosphors in H3 PO4 /KHF2 liquid instead of the hypertoxic HF liquid. The impact factors, such as the amount of F source, the reaction temperature, reaction time, and the luminescence mechanism are investigated in detail. We found that K2 TiF6 : Mn 4+ shows pure red emission and can be excited by blue lights, which can perfectly match the InGaN chip based white light-emitting diodes. Most importantly, K2 TiF6 : Mn 4+ exhibits excellent quenching behavior and shows small color shift in the temperature range of 300–475 K. Our researches could provide a green synthetic strategy to obtain the K2 TiF6 : Mn 4+ phosphors and contribute to the optimization of red phosphors for white light-emitting diodes.